Ética da alteridade no cuidado de enfermagem em hospital de ensino no Ceará - Pereira, Maria Dayse (2009)
The practice of ethical Nursing care within health services, particularly in public hospitals of Education, comes as part of collective work in health, incorporating technical, managerial, educational, social and political. The ethical dimension of alterity of care in this work scene, assumes the configuration of an attitude of respect and welcome the other, and promotes a continous refletction and changing of attitude of nursing professionals. The aim of this study is to understand the design ethic of care in the daily experience of nursing in the University Public Hospital, with ethical discussion of radical alterity in Emmanuel Lévinas. Descriptive in nature, this study is based on the Hermeneutic-phenomenology, with a qualitative approach. The seizure of the empirical data was achieved with nine nurses of the hospital staff, using the technique of individual interview. The analysis revealed evidence of three areas: care, ethics and otherness of Nursing. Under such dimensions, the data analysis allowed us to identify the importance of ethics of alterity in nursing care, the search for the organization of the care and management, the training, the interdisciplinarity of the shares through the mobilization and articulation of knowledge, the ethical and responsible care, the attitude of understanding the importance of quality care, the commitment to the subjectivity of care, highlighted by the interviewees. However, these workers live, now, with the contradictions inherent in the process of their work, emphasizing the care model that persists in transit between the model and fully functional in form and curative hospital. The management model prints, even today, the characteristics of mechanistic and fragmented work, the multidisciplinary and its relationship with the hierarchy of care, rather than interdisciplinarity; the suffering occupational derivative inadequate working conditions; progressive deficit of the workforce and increased absenteeism, and change the current organizational structure to support the tension between the handle and manage. Because of this scenario, it can be concluded that the Nursing resist, so purposeful, to these challenges, with strong evidence on ethical alterity of care. This trend can express the reflection for the reinvention of the social practice of care, beyond the classical approach of partial care for the size of alterity ethics of care